Evaluation of Waiting Time Prescription Services in Hospital Pharmacy Installations in the Tasikmalaya Area - Nita Asiah; Marlina Indriastuti (LPPM STIKes Muhammadiyah Ciamis, 2023)
Pharmaceutical Services in Hospitals are part which is inseparable from the Home health service Hospital System that is oriented towards patient service, provision pharmaceutical preparations, medical devices and consumable medical materials quality and affordable for all levels of society. The aim of this research is to determine the suitability of the waiting timer for recipe service at Medika Citratama Hospital in Tasikmalaya base on Minister of Health Regulation No.129/Menkes/SK/II/2008, namely the waiting time for concoction 60 minutes and non-concoction waiting time 30 minutes. The research method is descriptive by making observations or observing directly using observation. Data taken were 370 outpatient prescriptions, consisting of 270 non-concocted and 90 concocted prescriptions. The average waiting time for prescription services is 26.30 minutes for non-mixed prescriptions and 52.20 minutes for prescriptions. concoction.